Sloganization in language education discourse conceptual thinking in the age of academic marketization - Schmenk, Barbara; Breidbach, Stephan; Kèuster, Lutz (Multilingual Matters, 2019)
"This volume focuses on sloganization as an emergent phenomenon in language education discourse. Motivated by an increasing uneasiness with a number of concepts in current research that have become sloganized, this volume scrutinizes the discourse of language education, identifies popular slogans and reconstructs the sloganization processes"--Provided by publisher.